A detailed assignment of NEXAFS resonances of imidazolium based ionic liquids. Issue 12 (7th March 2016) - Ehlert, Christopher; Holzweber, Markus; Lippitz, Andreas; Unger, Wolfgang E. S.; Saalfrank, Peter
Abstract : Experimental and theoretical investigation of Near Edge Absorption Fine Structure (NEXAFS) resonances of two kinds of imidazolium based ionic Liquids. Abstract : In Near Edge X-Ray Absorption Fine Structure (NEXAFS) spectroscopy X-Ray photons are used to excite tightly bound core electrons to low-lying unoccupied orbitals of the system. This technique offers insight into the electronic structure of the system as well as useful structural information. In this work, we apply NEXAFS to two kinds of imidazolium based ionic liquids ([C n C1 im] + [NTf2 ] − and [C4 C1 im] + [I] − ). A combination of measurements and quantum chemical calculations of C K and N K NEXAFS resonances is presented. The simulations, based on the transition potential density functional theory method (TP-DFT), reproduce all characteristic features observed by the experiment. Furthermore, a detailed assignment of resonance features to excitation centers (carbon or nitrogen atoms) leads to a consistent interpretation of the spectra.